Programmed Topographic Substrates for Studying Roughness Gradient-Dependent Cell Migration Using Two-Photon Polymerization - Shivani, Subhashree; Hsu, Yu-Hsiang; Lee, Cheng-Je; Cheong, Chi-Sheng; Chung, Tien-Tung; Wang, An-Bang (Frontiers in Cell and Developmental Biology, 2022)
The mediation of extracellular matrix is one of major environmental cues to direct cell migration, such as stiffness-dependent durotaxis and adhesiveness-dependent haptotaxis. In this study, we explore another possible contact guidance: roughness-dependent topotaxis. Different from previously reported studies on topotaxis that use standard photolithography to create micron or sub-micron structures that have identical height and different spatial densities, we develop a new method to programmatically fabricate substrates with different patterns of surface roughness using two-photon polymerization. Surface roughness ranging from 0.29μm to 1.11μm can be created by controlling the voxel distance between adjacently cured ellipsoid-voxels. Patterned Ormocomp® masters are transferred to polypropylene films using nanoimprinting method for cell migration study. Our experimental results suggest that MG63 cells can sense the spatial distribution of their underlying extracellar roughness and modulate their migration velocity and direction. Three characteristic behaviours were identified. First, cells have a higher migration velocity on substrate with higher roughness. Second, cells preferred to migrate from higher roughness to lower roughness regions, and their migration velocity also decreased with descending roughness. Third, the migration velocity remained unchanged on lower roughness range on a graded substrate with a steeper roughness. The last cell migration characteristic suggest steepness of the roughness-gradient can be another environmental cue in addition to surface roughness. Finally, the combination of two-photon polymerization and nanoimprint methods could become a new fabrication methodology to create better 3-D intricate structures for exploring topotactic cell migrations.